O bairro está on-line? Vivências e sociabilidade(s) juvenis em um bairro da região metropolitana de Belo Horizonte - Reis, Juliana Batista dos (Universidade Federal de São Carlos, 2009)
Is it possible to think about periphery on Internet? From a ethnographic view, this research aims to describe some youth practices which supposes the formation of ties and relations implying determined ways of understanding a Belo Horizonte's "peripheral" region: a neighborhood on Nova Contagem. To comprehend the dynamics of socialization process and sociability, we, privilege two observational "places": a LAN gaming center and virtual communities about Nova Contagem on website Orkut (www.orkut.com). The research reveals a intense on-line interaction between the youth who lives on the same neighborhood, besides virtual communities created in virtue of this belonging. The notion of periphery is discussed as analysis' category, spatial reference, as well as its symbolic senses presents on youth s testimony. We try to reveal the interfaces and (dis)continuity between the Internet meetings and face-to-face meetings at LAN gaming Center and other activities on neighborhood.
Keywords: Antropologia urbana; Sociabilidade; Periferia urbana; Internet; Jovens; Sociability; Periphery; Internet; Youth; CIENCIAS HUMANAS::SOCIOLOGIA